2009
DOI: 10.1016/j.ijgo.2009.03.016
|View full text |Cite
|
Sign up to set email alerts
|

Compared effects of surgical and natural menopause on climacteric symptoms, osteoporosis, and metabolic syndrome

Abstract: Compared with natural menopause, surgical menopause was found to be associated with higher rates of climacteric symptoms and osteoporosis but not of metabolic syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
2
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 19 publications
3
32
2
1
Order By: Relevance
“…It is not the absolute level of estrogens, but the rate of estrogen withdrawal that determines the onset of flushes (Kronenberg, 2010; Santoro, 2008). As an example, the abrupt hormone withdrawal after oophorectomy (‘‘surgical menopause’’) is associated with increased severity and frequency of hot flushes (Casper and Yen, 1985; Gelfand, 1999; Özdemir et al, 2009). Hot flushes do not occur in situations where estrogen is chronically absent from birth, unless exogenous estrogens are administered and then subsequently withdrawn (Kronenberg, 1994).…”
Section: Physiology Of Hot Flushesmentioning
confidence: 99%
“…It is not the absolute level of estrogens, but the rate of estrogen withdrawal that determines the onset of flushes (Kronenberg, 2010; Santoro, 2008). As an example, the abrupt hormone withdrawal after oophorectomy (‘‘surgical menopause’’) is associated with increased severity and frequency of hot flushes (Casper and Yen, 1985; Gelfand, 1999; Özdemir et al, 2009). Hot flushes do not occur in situations where estrogen is chronically absent from birth, unless exogenous estrogens are administered and then subsequently withdrawn (Kronenberg, 1994).…”
Section: Physiology Of Hot Flushesmentioning
confidence: 99%
“…Animal studies have consistently demonstrated a relationship between bilateral oophorectomy and increased adiposity (1315) and insulin resistance (13, 16, 17) and higher total and LDL-cholesterol (13, 18). A few clinical studies and two population based studies have examined the association of oophorectomy with weight, body mass index (BMI), and waist circumference (WC), however the results have been inconsistent (12, 1924), No study has specifically evaluated body fat as measured by bioelectrical impedance analysis (BIA). BIA measures the opposition of body tissue to the flow of a small electric current, which can be used to estimate total body water, fat free mass, and percent body fat.…”
Section: Introductionmentioning
confidence: 99%
“…In addition the surgical menopause was more frequent in MS + sample with respect MS − sample, however it did not result a direct predictor for MS, in according with previous studies [32]. The difference observed thus is probably related to the effect of years since menopause: in fact surgical menopause usually occurs before than physiological menopause.…”
Section: Discussionmentioning
confidence: 43%